Persistent fetal haemoglobin and falsely high glycosylated haemoglobin levels. Issue 6440 (4th August 1984) - Paisey, R B; Read, R; Palmer, R; Hartog, M
Abstract : Some of the routine methods of measuring glycosylated haemoglobin depend on its difference in charge from haemoglobin A and do not distinguish between glycosylated haemoglobin and fetal haemoglobin. Two insulin dependent diabetics showed persistent discrepancies between their capillary blood glucose values and their glycosylated haemoglobin values measured by agar gel electrophoresis: the blood values were normal but the glycosylated haemoglobin values were raised. In one patient increases in insulin dose in response to the glycosylated haemoglobin results repeatedly produced hypoglycaemia. Both patients were found to have higher than normal concentrations of fetal haemoglobin; and when measured by the thiobarbituric acid reaction their glycosylated haemoglobin levels were almost normal. This problem may be avoided by using a method that distinguishes between fetal and glycosylated haemoglobin or by testing glycosylation of hair or serum albumin if discrepancies arise. This is particularly important during pregnancy, when some women have an increase in fetal haemoglobin.